2011
DOI: 10.1002/cjce.20503
|View full text |Cite
|
Sign up to set email alerts
|

The effect of off‐wall clearance of a side‐entering impeller on the mixing of pulp suspensions in a cylindrical stock chest

Abstract: For a side-entering impeller of diameter D, the clearance from the off-wall (E) is characterised by E/D and it affects the mixing quality attained in a pulp stock chest. For agitation of pulp suspensions, mixing can be characterised by the size of cavern produced by the impeller. In this work, we have investigated cavern size as a function of the impeller off-wall clearance in a laboratory-scale cylindrical stock chest. Hardwood pulp suspensions of C m = 2%, 3%, and 4% (fibre mass concentration) were agitated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…1). The E/D ratio (clearance from rear-wall to impeller diameter ratio) was set to 0.56 based on the results presented by [9,33,44].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). The E/D ratio (clearance from rear-wall to impeller diameter ratio) was set to 0.56 based on the results presented by [9,33,44].…”
Section: Methodsmentioning
confidence: 99%
“…Due to the wide variety of mixing requirements, many variations of the constituent parts of the stirred tank have arisen. It has been shown that operating conditions and geometrical properties of the impeller and vessel define the fluid dynamic inside the tank [9,25,34,42]. For instance, flow patterns of axial and hydrofoil impellers are characterized by one main circulation loop, and high velocities near the blade tip.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important parameter, affecting power consumption and flow pattern is the impeller location. There are some guidelines in literature for impeller clearance (distance between the impeller and vessel rear wall) based on empirical work . However, their applicability might be limited to specific conditions, since the optimum dimensionless clearance E/D (where E is the clearance from rear‐wall, and D is the impeller diameter) is a function of operating conditions, rheology, and mechanical constraints.…”
Section: Introductionmentioning
confidence: 99%
“…However, their applicability might be limited to specific conditions, since the optimum dimensionless clearance E/D (where E is the clearance from rear‐wall, and D is the impeller diameter) is a function of operating conditions, rheology, and mechanical constraints. Bhole et al used electrical resistance tomography to identify dead zones inside a stock chest and showed that for a 3% hardwood pulp suspension the optimal E/D ratio is close to 0.5. Moreover, they found a substantial restriction of the flow to the impeller suction at E/D = 0.14, which leads to an increase of the power requirements.…”
Section: Introductionmentioning
confidence: 99%